PENGARUH BERMAIN GAME ONLINE TERHADAP PRESTASI BELAJAR SISWA DI SD - Eriska Siburian; Jontra Jusat Pangaribuan; Antonius Remigius Abi; Patri Janson Silaban (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article reports the effect of playing online games on students’ learning achievement at Wesley 2 Private Elementary School Tanjung Morawa in Deli Serdang in the academic year 2021/2022. The research used a descriptive-analytical research method. The research population involved 31 students, which consisted of 3 classes, class III, IV, and V at Wesley 2 Private Elementary School Tanjung Morawa in Deli Serdang. The sampling technique used purposive sampling. The results indicated that the results of the correlation test can be seen in the correlation coefficient value of -0.832 where rcount (-0.832) > rtable (0.355), thus, it could be concluded that the alternative hypothesis (Ha) was accepted. It means that there is a significant negative effect between playing online games and students’ learning achievement at Wesley 2 Private Elementary School Tanjung Morawa in Deli Serdang. It can also be seen from the results of the t-test where tcount > ttable. It was obtained tcount of -8.074. If it was customized with the value of ttable on degrees of freedom (df) = 29 of 1.699, which was tcount (-8.074) > ttable (1.699), thus, the alternative hypothesis (Ha) was accepted. It shows that there was a significant positive effect of playing online games on the learning achievement of Wesley 2 Private Elementary School students Tanjung Morawa in Deli Serdang in the academic year 2021/2022.